Memórias de superação: narrativa de si e trajetória formativa em Pedagogia - Santos, Maria Silvana Silva dos (Brasil, 2024)
In this memorial I present a description of the most relevant facts of my personal and academic journey. Thus, I tried to record relevant facts and events from my life path, from childhood to academic life with the aim of making a genuine memory of my memory, rescuing my past, especially my childhood, with experiences and reflections of great importance for me. today's day. I see that it is extremely important to deal with people who go through what I went through as a child. There were many obstacles overcome in my school career: Elementary School, High School and Higher Education. I understand that as a human being and citizen it is necessary to go through several stages of personal, social and intellectual development, considering that the challenges of childhood contribute to the following stages of adult life. I can say that this Descriptive Memorial reveals impactful facts not only about my educational background, but also about my family and personal trajectory. Today I present it with enormous satisfaction, as I have reached the end of this long-awaited training that has already contributed and will contribute much more to my teaching career, being the realization of a dream to obtain higher education. During my training, I built knowledge and acquired great learning through the assimilation of the theories and practices of the Degree in Pedagogy.